Assessment of Housing Attributes Towards Neighbourhood Satisfaction in The Klang Valley - Roslan, Siti Nurul Munawwarah; Wan Abd Aziz, Wan Nor Azriyati; Kari, Fatimah; Mohd Satar, Nurulhuda (International Journal of Property Sciences (E-ISSN: 2229-8568), 2019)
Housing has always been one of the major issues that affect peoples’ quality of life, especially in the urban area. The increased number of population in urban area led to an increase in housing demand in the market. Neighbourhood satisfaction is an important factor of housing demand in urban areas. The objective of this study is to assess the relationship between housing attributes and neighbourhood satisfaction in the Klang Valley, Malaysia. Primary data collection through survey on 500 respondents was undertaken and analysed using SPSS and Structural Equation Modelling. The findings revealed that there is positive and significant relationship between housing attributes and neighbourhood satisfaction. The implication of this study found that housing attributes are noteworthy determinants in assessing the significance of neighbourhood satisfaction. The result of this study would assist policy making in proposing actual improvement in sustainable development in neighbourhood area and enhance on the improvement on the housing attributes that focus on providing more affordable housing and housing choice in the Klang Valley.